2019
DOI: 10.1186/s12889-019-7814-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with tuberculosis disease among children who are household contacts of tuberculosis cases in an urban setting in Malaysia

Abstract: BackgroundWith the rise in prevalence of childhood tuberculosis (TB) globally, contact tracing should be a powerful strategy for early diagnosis and management, especially in children who are household contacts of active TB cases. Here, we aimed to determine the prevalence and factors associated with TB disease in children who are household contacts of TB cases.MethodsWe used a cross-sectional study with data from the Malaysian TB Information System (TBIS) recorded from 1 January 2014 to 31 December 2017. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…However, datasets used for analysis in this study are not publicly available due to some concern, in which it contained health information which could compromise the privacy of research participants. Details on TBIS also have been cited in few other studies related to TB in Malaysia [24][25][26].…”
Section: Data Collectionmentioning
confidence: 99%
“…However, datasets used for analysis in this study are not publicly available due to some concern, in which it contained health information which could compromise the privacy of research participants. Details on TBIS also have been cited in few other studies related to TB in Malaysia [24][25][26].…”
Section: Data Collectionmentioning
confidence: 99%
“…In a prospected cohort study in the central parts of Iran carried out by Aminzadeh et al, two of 23 closed contact children developed active tuberculosis, while in another study conducted by Kontturi in Finland, 34 of 526 children exposed to TB cases showed positive criteria for active disease [2] , [14] . Also, a study in Malaysia that examined 2793 children aged 0–14 in close contact with at least one case of TB, the prevalence of active TB was 1.5 % [15] . Lower rate of pathogenicity of tuberculosis among the exposed children in our study area can be due to good care and follow up of TB patients and their families in the PHC system of Iran particularly in the most prevalence areas.…”
Section: Discussionmentioning
confidence: 99%
“…It is mandatory to notify TB cases once any medical officers make a diagnosis in both private and public healthcare facilities. Details on the TBIS have been published elsewhere [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Type of residence was categorised into low-cost, medium- to high-cost, and other. Low-cost residences were defined as low-cost flats and residence under the government housing programs ( Projek Perumahan Rakyat , PPR ) [ 18 ]. Medium- to high-cost residences were defined as apartments, condominiums, terrace houses and bungalows.…”
Section: Methodsmentioning
confidence: 99%